The subsistence fisheries in Batanes Islands, Philippines. - Obar, l Andro A. (2020.)
Subsistence fishery refers to a sub-component of the small-scale fishery sector that essentially supports the food requirements of dependent fishers. The activities of subsistence fishers include fishing and gleaning, and these allow them to be resilient especially when faced with natural and anthropogenic events. For an archipelagic country like the Philippines, most fishers residing in small inland communities throughout the country rely on activities that are considered subsistence fisheries. However, in areas where these activities matter, studies are either few or outdated. This particular study focuses on the subsistence fishery of Batanes Province, which is composed of six small-island communities dispersed in three islands that are located in one of the major fishing grounds of the country. In Batanes, subsistence fishery is very common. Ivatans continue to use up to 21 types of simple and traditional fishing gears and methods. With or without the use of fishing boat and gear, a subsistence fisher can produce or gather ten (10) kilograms of fish and other fishery resources. apart from finfish, typically harvested resources from 2-3 hours of fishing and gleaning activities include mollusks, such as bivalves, shells, squid, octopus, and cuttlefish; crustaceans, like spiny lobster, slipper lobster, and crabs; and seaweeds, specifically Caulerpa spp., Codium edule, Gracillaria edulis and Ulva sp.). Women, men, and children of different age groups participate in this type of fisheries. The study is increasing relevant, especially in a changing climate regime, because it fills in data gaps about this segment of the municipal fishery sector, which already include among the poorest in Philippine society today; it gives opportunities fo government to respond to the needs of their dependents promptly, especially during periods of disasters; and it allows researchers to discover potential resources of high economic value while they are still close to their pristine state.
Thesis (M.S. Fisheries-Fisheries Biology) -- [Miagao, Iloilo] : University of the Philippines Visayas, June 2020.
Keywords: Subsistence fishery